‘Science is purely about the truth so I don’t think you could compare it to non-truth versus the truth.’ Students’ perceptions of religion and science, and the relationship(s) between them: religious education and the need for epistemic literacy - Fraser-Pearce, Jo (British Journal of religious education, 2021)
There already exists a large knowledge base about teaching and learning related to the origins, diversity and history of life on Earth. We know less about teaching and learning related to wider issues pertinent to both religion and science. In our research with 40 students in six secondary schools in England, we looked at wider issues of student perceptions of religion and science. Our study involved an intervention of six lessons in Science and six in Religious Education (RE). Issues of philosophy, including ethics, were raised in Science lessons. The RE lessons dealt with a variety of contexts that highlighted the question of the relationship(s) between religion and science. In both pre- and post-intervention interviews, we found many instances where students used language that conveyed a misconception of the epistemic distinctions between religion and science. Students referred to ‘truth’, ‘theory’ and ‘facts’ interchangeably when discussing religious and scientific knowledge. We argue that RE needs to attend to epistemic literacy if we are to both avoid epistemological misconceptions and enable students to develop insights into the specific knowledge forms manifested in religion(s).